Christmas stories - Tesdell, Diana Secker (New York : Knopf, 2007)
A collection of twenty Christmas stories written by nineteenth and twentieth-century authors, including Charles Dickens, Anton Chekhov, Leo Tolstoy, and John Cheever.
The story of the goblins who stole a sexton (from The Pickwick papers) / Charles Dickens -- The night before Christmas / Nikolai Gogol -- The blue carbuncle / Arthur Conan Doyle -- Christmas at Thompson Hall / Anthony Trollope -- Where love is, God is / Leo Tolstoy -- Vanka / Anton Chekhov -- The burglar's Christmas / Willa Cather -- A chapparal Christmas gift / O. Henry -- Reginald's Christmas revel / Saki (H.H. Munro) -- Christmas / Vladimir Nabokov -- Dancing Dan's Christmas / Damon Runyon -- Bella Fleace gave a party / Evelyn Waugh -- Green holly / Elizabeth Bowen -- Christmas is a sad season for the poor / John Cheever -- A Christmas memory / Truman Capote -- The carol sing / John Updike -- Christmas fugue / Muriel Spark -- The loudest voice / Grace Paley -- The turkey season / Alice Munro -- Crèche / Richard Ford.
Adult.
Adult
Keywords: Christmas stories; Short stories; Christmas -- Fiction; Short stories